(untitled) (Kinesiology, 2020)
In 2015, 120 central primary schools in Croatia failed to meet the minimum requirements, and could not carry through the full-time compulsory Physical Education class. To ensure daily habits for physical exercise in all children and help teachers, Croatian Institute of Public Health has designed a Set of kinesiological aids and implemented the project “Polygon for Physical Activity of School-Aged Children”. The aim of this paper is to present the results of Project evaluation. Project evaluation has shown improved conditions and increased pupil interest in Physical Education. A statistically significant difference (χ2=65,30, df=4, p<0,001) was noted in teachers perception concerning the suitability of equipment for the youngest pupils before and after the project. The Set was regularly used by 85.59% teachers, whereof 82.88% believed that the pupils loved it. Most teachers estimated that this project could help advance the quality of the Physical Education class, and would recommend this Set. This project is a positive innovation for the teaching process and a strong potential for alleviating the spatial-material problems many schools are experiencing.